1972
DOI: 10.1161/01.cir.45.2.335
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Isoproterenol, l -Norepinephrine, and Intraaortic Counterpulsation on Hemodynamics and Myocardial Metabolism in Shock following Acute Myocardial Infarction

Abstract: SUMMARYThe effects of isoproterenol, l-norepinephrine, and intraaortic counterpulsation on hemodynamics and myocardial metabolism were evaluated in shock due to acute myocardial infarction. Before treatment, the cardiac index was markedly reduced, averaging 1.35 liters/min/m2. Mean aortic pressures ranged from 40 to 65 mm Hg.Decreases in coronary blood flow (mean, 68 ml/100 g/min) and in myocardial oxygen consumption (mean, 8.11 ml/100 g/min) were associated with abnormally high myocardial oxygen extractions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
7

Year Published

1975
1975
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(28 citation statements)
references
References 38 publications
1
20
0
7
Order By: Relevance
“…Our results with intraaortic counterpulsation alone are comparable to those of other reported series8 9, [16][17][18][19] and the outcome, in some respects, is more favorable.…”
Section: Comparison With Other Studiessupporting
confidence: 89%
See 3 more Smart Citations
“…Our results with intraaortic counterpulsation alone are comparable to those of other reported series8 9, [16][17][18][19] and the outcome, in some respects, is more favorable.…”
Section: Comparison With Other Studiessupporting
confidence: 89%
“…Of the five long-term survivors, two had previous infarc- The major determinant of a favorable result in group 2 (table 4) appeared to be the time from the onset of infarction to the institution of treatment with bypass grafting and counterpulsation. The subset of patients treated more than 18 hours after the onset of infarction had a 71.4% (five of seven) in-hospital mortality, while the patients treated within 16 hours had a 25% (three of 12) mortality rate. No patient was treated between 16 and 18 hours from the onset of infarction.…”
Section: Mortality In Groupmentioning
confidence: 95%
See 2 more Smart Citations
“…Studies with pure va soconstrictors such as methoxamine showed that arterial pressure and peripheral resis tance could be increased in cardiogenic shock but that cardiac output was simulta neously decreased [10], Isoproterenol in creased cardiac output, but at the expense of increased heart rate and decreased coro nary perfusion pressure, while norepineph rine, which has both alpha-and beta-agonistic properties, increased both arterial pressure and cardiac output [11,12]. Thus, norepinephrine emerged as the agent of choice for the initial treatment of shock complicating myocardial infarction.…”
Section: The Early Periodmentioning
confidence: 99%